Language Proficiency, Parenting Styles, and Socioemotional Adjustment of Young Dual Language Learners. (August 2019) - Chung, Sara; Zhou, Qing; Anicama, Catherine; Rivera, Carol; Uchikoshi, Yuuko
Dual language learners (DLLs) make up 32% of all children in the United States. Past research showed that proficiency in a heritage language (HL) was associated with better psychological adjustment in school-aged children and adolescents, but the associations of HL and English (EL) proficiency with preschool-aged DLLs' socioemotional adjustment remain understudied. This study included a sample of low-income Mexican and Chinese immigrant families with preschool-aged DLLs ( N = 90). Children's HL and EL proficiencies were assessed using language tests. Parents rated their own cultural orientations, parenting styles, and children's socioemotional adjustment. Children's expressed anger/frustration and sadness were observed from an emotion-evoking task. Path analyses were conducted to test (a) the unique relations of children's HL and EL proficiency and parents' American and heritage cultural orientations to parenting styles, and (b) the relations of parenting styles to children's adjustment. Results showed that children's expressive HL proficiency and parents' American and heritage cultural orientations were positively associated with authoritative parenting, which in turn was associated with children's lower externalizing problems and higher prosocial behaviors. Children's expressive EL was negatively associated with parents' use of authoritarian parenting, and both expressive and receptive HL were negatively associated with children's expressed sadness. These results indicate that children's HL development and parents' host and heritage cultural orientations are associated with socioemotional benefits for young DLLs growing up in low-income immigrant families.